The application of computational fluid dynamics to the modelling and design of high-speed boats - JACK TOWNSEND (2021)
Computational ﬂuid dynamics solvers were applied to the ﬁeld of high-speed boat design. The lattice Boltzmann method was used to assess the water-phase of the ﬂow around a number of high-speed hullform geometries, and was validated against empirical industry and literature data. A heave dynamics capability was developed to assess the heave equilibrium position of a high speed boat, showing close agreement with industry data. A mesh movement and evolutionary optimisation software was applied to the aero-dynamic optimisation of a high-speed catamaran using a Reynolds-averaged Navier-Stokes solver for modelling of the air phase of the ﬂow.